COLLABORATIVE STRATEGIC READING TO IMPROVE STUDENTS’ READING COMPREHENSION - Susana Aulia; Mutmainnah Mustofa; Imam Wahyudi Karimullah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The aims of this research is to improve students’ reading comprehension using Collaborative Strategic Reading. The method used in this research is experimental research with one group pre-test posttest design. The populations in this study were fourth semester students of the Department of English Education in the academic year 2019/2020. The sampling technique used was cluster random sampling. Data collection techniques are tests and observation. Data analysis technique used is Paired sample t-test.The result shows that the average value of the post-test reading comprehension was higher than the results of the pretest reading comprehension (81,250> 51,875). From the mean data obtained it can be seen that there are differences in reading comprehension students of English Education with Collaborative Strategic Reading (CSR) techniques. In addition, it was proven statistically, the results of the paired sample t-test revealed that the value of thitung obtained was 30,371 or thitung greater than ttabel (30,371> 1,684). In addition, the significance value obtained was 0,000 or the significance value was smaller than the significance standard of 0.05 (sig <0.05). Thus, it indicates that Collaborative Strategic Reading (CSR) learning model can improve reading comprehension students of English Education in Islamic University of Malang. Key words: Collaborative Strategic Reading, Reading Comprehension, Teaching Strategy